Comparison of extraction techniques for isolation of steroid oestrogens in environmentally relevant concentrations from sediment. Issue 11 (1st September 2016) - Sadílek, Jan; Spálovská, Petra; Vrana, Branislav; Vávrová, Milada; Maršálek, Blahoslav; Šimek, Zdeněk
ABSTRACT: The comparison of four extraction techniques for isolation of five native and one labelled steroid oestrogens from sediment was described. The three conventional extraction techniques Soxhlet warm extraction (SWE), accelerated solvent extraction (ASE), microwave-assisted extraction (MAE) and a promising technique QuEChERS were tested for isolation of low environmentally relevant oestrogen concentrations using different extraction conditions. The least expensive and time-consuming method QuEChERS provided the best extraction recoveries (53–84%) from all techniques. MAE achieved the highest recovery from conventional techniques for less polar oestrogens using dichloromethane: acetone 3:1 mixture as an extraction solvent (50–71%), but for extraction of the whole group of oestrogens including more polar estriol acetone or methanol must be used. ASE provided higher extraction recoveries using dichloromethane at 60°C (53–74%) for less polar oestrogens. However, the repeatability of results was unsatisfactory and recoveries using other extraction conditions were lower than for MAE. The most time-consuming SWE achieved the worst extraction recoveries and for isolation of low oestrogen concentrations from sediments, it is completely unsuitable.